2013
DOI: 10.22499/2.6301.013
|View full text |Cite
|
Sign up to set email alerts
|

The relative performance of Australian CMIP5 models based on rainfall and ENSO metrics

Abstract: We assess the performance of 30 CMIP5 and two CMIP3 models using metrics based on an all-Australia average rainfall and NINO3.4 sea surface temperatures (SSTs). The assessment provides an insight into the relative performance of the models at simulating long-term average monthly mean values, interannual variability and the seasonal cycles. It also includes a measure of the ability to capture observed rainfall-NINO3.4 SST correlations. In general, the rainfall features are reasonably simulated and there is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The correlation coefficients between the seasonal ERA5 NINO34* and rainfall are given in Table 2. The strongest link is in SON, with r ¼ −0.61 (with a variation through the year like that of the monthly results from Smith et al, 2013). However, only in MAM does the regression line provide a substantial percentage (55%) of the (relatively small) 2019 pr anomaly (as seen in Figure S2d).…”
Section: Standard Driver Indices 331 Nino34mentioning
confidence: 80%
See 1 more Smart Citation
“…The correlation coefficients between the seasonal ERA5 NINO34* and rainfall are given in Table 2. The strongest link is in SON, with r ¼ −0.61 (with a variation through the year like that of the monthly results from Smith et al, 2013). However, only in MAM does the regression line provide a substantial percentage (55%) of the (relatively small) 2019 pr anomaly (as seen in Figure S2d).…”
Section: Standard Driver Indices 331 Nino34mentioning
confidence: 80%
“…An ENSO index previously linked to All-Australia rainfall by Smith et al (2013), NINO34, is based on the temperature for the central Pacific region shown in Figure 1. For the purpose of assessing links in ERA5, this and other indices are determined directly from the ERA5 fields.…”
Section: Standard Driver Indices 331 Nino34mentioning
confidence: 99%
“…The CAPTIVATE tests are then applied, targeting features of the mean state climatology (CLIM, retaining the short names used extensively in the project), variability (VAR) and teleconnections (TELE) that are important to Australian climate. A further assessment of the CMIP5 models by Smith et al (2013) can be found in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…We leave out the discussion of the simulated surface climate, as this will be discussed elsewhere. For example, the global surface climate is described in Bi et al (2013), Dix et al (2013), Smith et al (2013) and , the land-surface climate in Kowalczyk et al (2013), while the interannual variability associated with the El Niño−Southern Oscillation (ENSO) events is documented in Rashid et al (2013). Our main focus here is to document the fidelity of ACCESS-CM in simulating the key atmospheric circulation systems.…”
Section: Model Experiments and Validation Datamentioning
confidence: 99%